Fish Aggregation Pattern on Red-Blue-Green Light Emitting Diode (RGB-LED) Light in Static Lift Net - Sugandi Sugandi; Ronny Irawan Wahju; Mochammad Riyanto; sumardi sumardi (Journal Omni-Akuatika, 2019)
The Red-Blue-Green Light Emitting Diode (RGB-LED) light used in the static lift net can manipulate fish behavior to attract, approach and be concentrated in the lighting area. The purpose of this study is to determine the use of the RGB-LED light intensity with pulse width modulation PWM) value for gathering fish and changing patterns of schooling fish’s movement. Seven treatments with changes in PWM values were the initial conditions, 250, 195, 145, 95 20 and 5 PWM. The methods were by using Hydro-acoustic sonar 360o and ImageJ analysis used to determine the schooling fish’s area in horizontal and vertical by dividing the center zone, main zone, influence zone, and shadow zone. Results of the visualization image of schooling fish as the target fish group visualized by horizontally and vertically. It has the longest duration of 90 ' and 250 PWM has a time duration of 10' shows the difference in the area of schooling fish in four zones. 195, 145 and 95 PWM with each time duration of 10' dominant schooling fish were in the main zone and influence zone, the lowest two light intensities of PWM values were 5 and 20, there are three zones namely center zone, main zone, and shadow zone, schooling fish were increasing with movement pattern by revolving the light source at shadow zone. The approached fish were forming schooling fish because they were attracted to light, with changes in the PWM value that can model the movement patterns of schooling fish.